Nauczyciel inicjatorem czytelnictwa uczniów klas początkowych - Radzikowska, Dorota (Nauczyciel wczesnej edukacji kreatorem środowiska edukacyjnego dziecka, 2016)
The article covers the issue of stimulating students reading interests by early education teachers. The author puts a thesis that one of the key conditions of making a child interested in reading is the appropriate choice of reading material. Such an action requires from the teacher working on two grounds: recognizing the addressee – the child, his development features, sensitivity, experiences from family home or the reading ability level and good knowledge of children’s literature (including the contemporary one), its features, assessment criteria, novelties appearing on the publishing market. According to the thesis the author gives several exemplary, moderns publications which might evoke reading interests in early education students.